ANALISIS FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA AUDITOR DAN HUBUNGANNYA DENGAN KINERJA DAN KEINGINAN BERPINDAH KERJA AUDITOR - Fitriany, Fitriany; Gani, Lindawati; Siregar, Sylvia Veronica; Marganingsih, Arywarti; Anggraita, Viska (UI Scholars Hub, 2011)
This research aims to examine the factors that influence auditor’s job satisfaction, the effects of job satisfaction on performance and turnover intentions, and how far the performances moderate the relationship between job satisfaction and turnover intention. The unit of analysis from this study is an auditor who works on a public accounting firm. Results showed that in small accounting firms, only consideration leadership style affects auditor’s satisfaction, while in big accounting firms, leadership style and structure leadership style have affected auditor’s satisfaction. Considerate Leadership style has higher effect than structural leadership style. For auditors in the big accounting firms, the higher the auditor's position, the greater the desire to leave accounting firms, but the longer the experience of the auditors, the lower the desire to move from the accounting firms. In this case it is necessary to have periodic promotion policy in the accounting firms. Job satisfaction has a positive influence on performance on all types of the accounting firms. If auditors are satisfied with the work, then their turnover intentions will be low. If auditors have low job satisfaction, they will leave the accounting firms, no matter their performance level because they only consider the accounting firms as stepping stone for their next career. So firms must consider auditors' job satisfaction if they do not want to lose their auditors.